Strategi Peningkatan Hasil Pertanian Perspektif Ekonomi Syariah (Studi Kasus Pertanian Padi Di Desa Ngalian) - Syukron, Muhammad; Adinugraha, Hendri Hermawan (Universitas Islam Negeri Sumatera Utara, 2024)
This research aims to find out the strategy of applying Islamic economic principles to increase the yield of rice farming. Rice is the staple food of the Indonesian people. Efforts to increase agricultural yields aim to meet domestic food needs and minimize import dependence. The majority of Indonesian people embrace Islam as their belief. The principles of Islamic economics are the rules of behavior patterns of Muslim communities in order to obtain salvation both in this life and the next. This research uses qualitative research methods by obtaining data derived from scientific literature studies. The results showed that the application of sharia economic principles in rice farming provides goodness. The three main principles that are practiced are divinity, justice, and freedom. Farmers in Ngalian village apply the principle of divinity by conducting tahlil religious ceremonies and praying together to ask Allah Swt to give smoothness. The principle of justice is practiced in the distribution of water and fertilizer subsidized by the government so that agriculture can be maximized by all farmers without any disadvantaged parties. The application of the principle of freedom also makes farmers free in carrying out the planting process without any pressure from a party.